Gradience in Grammar 2006
DOI: 10.1093/acprof:oso/9780199274796.003.0017
|View full text |Cite
|
Sign up to set email alerts
|

Prosodic Influence on Syntactic Judgements

Abstract: We argue for the importance of controlling prosody in soliciting syntactic judgments. Through the analyses of a variety of complex Wh-constructions in Japanese, we first attempt to reveal that a construction which requires a non-default prosody is vulnerable to misjudgments of syntactic wellformedness when it is presented to the subjects in writing. We then report on our pilot experiments on the comparison of grammaticality judgments of written and spoken sentences in both English and Japanese, which supports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(20 citation statements)
references
References 230 publications
(8 reference statements)
1
15
0
2
Order By: Relevance
“…(ii) 'What 1 is it that Naoya still remembers [whether Mari drank it 1 at the bar]?' Kitagawa and Fodor (2006) support this analysis with the results of their experiment investigating subjects' incremental parsing, in which sentences like (11), with Global FPd assigned, were accepted more often in listening than in silent reading. Note that the implicit Local FPd here would force the Wh-phrase na'ni 'what' to be associated with the declarative COMP -to 'that' in the subordinate clause and induce ungrammaticality, as was discussed for similar sentences in (7) and (8) above.…”
Section: Extra-grammatical Biases On Wh-scope Interpretationssupporting
confidence: 73%
See 2 more Smart Citations
“…(ii) 'What 1 is it that Naoya still remembers [whether Mari drank it 1 at the bar]?' Kitagawa and Fodor (2006) support this analysis with the results of their experiment investigating subjects' incremental parsing, in which sentences like (11), with Global FPd assigned, were accepted more often in listening than in silent reading. Note that the implicit Local FPd here would force the Wh-phrase na'ni 'what' to be associated with the declarative COMP -to 'that' in the subordinate clause and induce ungrammaticality, as was discussed for similar sentences in (7) and (8) above.…”
Section: Extra-grammatical Biases On Wh-scope Interpretationssupporting
confidence: 73%
“…If, on the contrary, this sentence is accompanied by Local FPd (that is, if the matrix item i'mademo 'even now' in these sentences does not undergo post-focal reduction and remains fully uncompressed), it would force the Wh-phrase to be associated with the declarative complementizer -to (-COMP That ) and the sentences become awkward and uninterpretable. This observation has been made by Deguchi and Kitagawa (2002:83) and, as discussed in Section 2.2.1 below, supported experimentally by Kitagawa and Fodor (2006). Thus, these researchers were led to conclude that it is a mistake to regard FPd as an exceptional intonational pattern that is appealed to only in order to override the Subjacency condition in cases like (3) and (6a).…”
Section: T D $ I N L I N E ]mentioning
confidence: 70%
See 1 more Smart Citation
“…Schütze (1996) exemplifies this difficulty in various domains, and argues that, in principle, it can be coped with by controlled acceptability rating experiments. A recent example with far-reaching theoretical consequences involves the discussion of wh-island constraints for in situ wh-phases in Japanese (Kitagawa and Fodor 2006;Ishihara 2005), where it could be shown that alleged subjacency effects on in situ wh-phrases do not exist. So-called "third-wh-effects" in English multiple questions also disappear under closer inspection (Clifton et al 2006;Fedorenko and Gibson 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Desde há muito, no entanto, diversos autores vêm questionando a confiabilidade dos dados informais de julgamento (cf. HILL, 1961;LABOV, 1996;SCHÜTZE, 1996;COWART, 1997;KITAGAWA;FODOR, 2006;FEATHERSTON, 2007;PHILLIPS, 2009;GIBSON;FEDORENKO, 2010, entre muitos trabalhos), apontando a sua instabilidade e consequente não confiabilidade, pelo menos como ponto de chegada das análises.…”
Section: Introductionunclassified